Depolarization-Mediated Regulation of Alternative Splicing - Sharma, Alok; Lou, Hua (Frontiers in Neuroscience, 2011)
Alternative splicing in eukaryotes plays an important role in regulating gene expression by selectively including alternative exons. A wealth of information has been accumulated that explains how alternative exons are selected in a developmental stage- or tissue-specific fashion. However, our knowledge of how cells respond to environmental changes to alter alternative splicing is very limited. For example, although a number of alternative exons have been shown to be regulated by calcium level alterations, the underlying mechanisms are not well understood. As calcium signaling in neurons plays a crucial role in essential neuronal functions such as learning and memory formation, it is important to understand how this process is regulated at every level in gene expression. The significance of the dynamic control of alternative splicing in response to changes of calcium levels has been largely unappreciated. In this communication, we will summarize the recent advances in calcium signaling-mediated alternative splicing that have provided some insights into the important regulatory mechanisms. In addition to describing the cis-acting RNA elements on the pre-mRNA molecules that respond to changes of intracellular calcium levels, we will summarize how splicing regulators change and affect alternative splicing in this process. We will also discuss a novel mode of calcium-mediated splicing regulation at the level of chromatin structure and transcription.